Realization of a push-me-pull-you swimmer at low Reynolds numbers. (11th September 2020) - Silverberg, O; Demir, E; Mishler, G; Hosoume, B; Trivedi, N; Tisch, C; Plascencia, D; Pak, O S; Araci, I E
Abstract: Locomotion at low Reynolds numbers encounters stringent physical constraints due to the dominance of viscous over inertial forces. A variety of swimming microorganisms have demonstrated diverse strategies to generate self-propulsion in the absence of inertia. In particular, ameboid and euglenoid movements exploit shape deformations of the cell body for locomotion. Inspired by these biological organisms, the 'push-me-pull-you' (PMPY) swimmer (Avron J E et al 2005 New J. Phys. 7 234) represents an elegant artificial swimmer that can escape from the constraints of the scallop theorem and generate self-propulsion in highly viscous fluid environments. In this work, we present the first experimental realization of the PMPY swimmer, which consists of a pair of expandable spheres connected by an extensible link. We designed and constructed robotic PMPY swimmers and characterized their propulsion performance in highly viscous silicone oil in dynamically similar, macroscopic experiments. The proof-of-concept demonstrates the feasibility and robustness of the PMPY mechanism as a viable locomotion strategy at low Reynolds numbers.